Mechanical characteristics of two environmentally friendly resins reinforced with flax fibers - Croccolo, Dario (Strojniški vestnik, 2015)
In this paper, a comparison between the mechanical characteristics of two different natural fiber composites has been carried out. The two composites were made using two different environmentally friendly resins, but with the same flax fiber reinforcement. Thirty-two specimens were tested for tension, bending and shear. The results obtained in the tensile and bending tests are acceptable according to the Standards, whereas those of the shear tests were discarded, since the samples exhibited unacceptable failure modes. In light of the results obtained, both in terms of strength and stiffness, the isophthalic resin (181EN2X) outperformed the vinyl ester resin (VEef220ST). In the case of the isophthalic resin, microscopic observations showed a good adhesion between the matrix and the fiber, with a small amount of air inclusions. The present study demonstrates that the mechanical characteristics of flax reinforced and environmentally friendly resins are similar to those achievable with the same fibers using conventional resins.
Keywords: deformacije; kompoziti z naravnimi vlakni; lan; mehanske lastnosti; napetosti; okolju prijazne smole